Association of Serum Antioxidant Vitamins and Carotenoids With Incident Alzheimer Disease and All-Cause Dementia Among US Adults. (24th May 2022) - Beydoun, May A.; Beydoun, Hind A.; Fanelli-Kuczmarski, Marie T.; Weiss, Jordan; Hossain, Sharmin; Canas, Jose Atilio; Evans, Michele Kim; Zonderman, Alan B.
Abstract : Background and Objectives: Serum antioxidant vitamins and carotenoids may protect against neurodegeneration with age. We examined associations of these nutritional biomarkers with incident all-cause and Alzheimer disease (AD) dementia among US middle-aged and older adults. Methods: Using data from the third National Health and Nutrition Examination Surveys (1988–1994), linked with Centers for Medicare & Medicaid follow-up data, we tested associations and interactions of serum vitamins A, C, and E and total and individual serum carotenoids and interactions with incident AD and all-cause dementia. Cox proportional hazards regression models were conducted. Results: After ≤26 years follow-up (mean 16–17 years, 7, 283 participants aged 45–90 years at baseline), serum lutein+zeaxanthin was associated with reduced risk of all-cause dementia (65+ age group), even in the lifestyle-adjusted model (per SD: hazard ratio [HR] 0.93, 95% CI 0.87–0.99; p = 0.037), but attenuated in comparison with a socioeconomic status (SES)–adjusted model (HR 0.92, 95% CI 0.86–0.93; p = 0.013). An inverse relationship was detected between serum β-cryptoxanthin (per SD increase) and all-cause dementia (45+ and 65+) for age- and sex-adjusted models (HR 0.86, 95% CI 0.80–0.93; p < 0.001 for 45+; HR 0.86, 95% CI 0.80–0.93; p = 0.001 for 65+), a relationship remaining strong in SES-adjusted models (HR 0.89, 95% CI 0.82–0.96; p = 0.006 for 45+; HR 0.88, 95% CI 0.81–0.96; p = 0.007 for 65+), but attenuated in subsequent models. Antagonistic interactions indicate putative protective effects of 1 carotenoid may be observed at lower levels other carotenoids or antioxidant vitamin. Discussion: Incident all-cause dementia was inversely associated with serum lutein+zeaxanthin and β-cryptoxanthin levels. Further studies with time-dependent exposures and randomized trials are needed to test neuroprotective effects of supplementing the diet with select carotenoids. Classification of Evidence: This study provides Class II evidence that incident all-cause dementia was inversely associated with serum lutein+zeaxanthin and β-cryptoxanthin levels.